(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2018)
The existence of Indonesia women through media has been pioneered by R.A Kartini who is known for hes ability in voicing his opinions and thoughts into her writing ability through letters. These letters in the present transformed into social media that became the medium of self-actualization of women. This Article focuses on how women educators in Makassar activity in the Facebook and Whatsapp. The study indicates that there are two main reasons why Facebook and Whatsapp are the preferred informative social media in this research, both of which are the most popular (because they are mostly used by one’s networking) and practical social media (because people can be easily found and to be found through these two social media and because of the facilities of these social media, they can share (like photos, documents, videos, etc.), and interact in various forms (such as video call, online games, etc.). Facebook and Whatsapp are used to connect each other, as the source of information, as an online shopping venue, a place hobby channeling, as well as a space to share moments. Their activities on Facebook and Whatsapp can be classified into silent readers, commentators, broadcasters, promoters, and owners of the stage. In fact, social media users are inversely proportional to the ability to understand Facebook and Whatsapp as ‘private spaces’ rather than as ‘public spaces’ where content are shared openly.